MiR-27b regulates podocyte survival through targeting adenosine receptor 2B in podocytes from non-human primate. Issue 11 (November 2018) - Zheng, Zuokang; Hu, Hong; Tong, Yanrong; Hu, Zhixia; Cao, Shiyu; Shan, Ce; Lin, Wenhe; Yin, Yike; Li, Zhonghan
Abstract MicroRNAs are a group of small non-coding RNAs that play key roles in almost every aspect of mammalian cell. In kidney, microRNAs are required for maintaining normal function of renal cells, disruption of which contributes to pathogenesis of renal diseases. In this study, we investigated the potential role of miRNAs as key regulators of podocyte survival by using a primary cell culture model from non-human primates (NHPs). Through microRNA profile comparison in glomeruli from mouse, rat and NHP, miR-27b was found to be among a list of glomeruli-enriched miRNA conserved across species. In NHP primary podocyte culture, significant downregulation of miR-27b was observed during treatment of puromycin aminonucleoside (PAN), a classic nephrotoxin. Overexpression of miR-27b enhanced PAN-induced apoptosis and cytoskeleton destruction in podocytes while its inhibition had a protective effect. Target identification analysis identified Adora2b as a potential direct target of miR-27b. Ectopic expression of miR-27b suppressed both Adora2b mRNA and protein expression, whereas inhibition of miR-27b increased the transcript and protein expression levels of Adora2B. Dual luciferase assay further confirmed Adora2b as a direct target of miR-27b. Furthermore, knockdown of Adora2b by siRNAs enhanced PAN-induced apoptosis, similar to the phenotypes we had observed with miR-27b overexpression. In addition, stimulating the adenosine signaling by an Adora2b agonist, NECA, improved podocyte survival upon PAN treatment. Taken together, our data identified a novel role of miR-27b-adora2b axis in primary podocyte survival upon injury and suggested a critical role of adenosine signaling pathway in podocyte protection.